A tapinocephalid dinocephalian (Synapsida, Therapsida) from the Rio do Rasto Formation (Paraná Basin, Brazil): Taxonomic, ontogenetic and biostratigraphic considerations. (November 2015) - Boos, A.D.S.; Kammerer, C.F.; Schultz, C.L.; Paes Neto, V.D.
Abstract: Permian tetrapod fossils have been recovered from the Rio do Rasto Formation of Brazil since the 1970s. Previous studies of this fauna indicated strong affinities with the Guadalupian-Lopingian vertebrates of South Africa and Eastern Europe, suggesting biostratigraphic correlations between these areas. Here, a new dinocephalian specimen from the Rio do Rasto Formation in the Serra do Cadeado area (Paraná State, Brazil) is described based on fragmentary skull remains and an associated left lower jaw ramus. Despite the fragmentary nature of these remains, they represent the most complete tapinocephalid specimen known from South America. Comparison with other tapinocephalids indicates that the material described herein represents a juvenile or sub-adult specimen. Although it is not possible to identify this material to the genus level, it most closely resembles the 'moschopines' Moschops and Moschognathus from the Tapinocephalus Assemblage Zone of South Africa. As dinocephalians are known to be restricted to the Guadalupian, they are one of the best tetrapod biostratigraphic markers for the Rio do Rasto Formation, indicating that at least some of the strata in the areas where they occur [Serra do Cadeado (Paraná State), Fagundes farm and Boqueirão farm (Rio Grande do Sul State)] are Guadalupian. Vertebrate fossils from Rio do Rasto Formation occur in disperse, isolated and discontinuous outcrops, so that they have been grouped in 'local faunas'. However, most of the specimens lack precise stratigraphic provenance data and even occurring in locations near each other they are not necessarily contemporary. Thus, until a more robust stratigraphic framework is developed, we suggest discontinuing use of 'local faunas' to this stratigraphic unit. Graphical abstract: Highlights: The use of local fauna to the tetrapod-bearing sites of the Rio do Rasto Fm is ended. Serra do Cadeado railway sites bear Guadalupian/Lopingian horizons. The most complete tapinocephalid of South America is described for the first time. It is a juvenile specimen and tapinocephalid ontogeny is partially explored.